To study the macro habitat of fishes of Narayani river - Sah, Saroj Prasad (BMC Journal of Scientific Research, 2018)
33 species of fishes are found in Narayani river. Most of the fishes are migratory. A large number of species are reported in mid water column. A few fish species are crevice of rocks and stones. Fishes are arranged in stratification pattern in Narayani River. Maximum fish species are encountered in Mid water column. Minimum fish species are reported in crevices of rocks and bottom of stream.